Western music by its others overseas Filipino musicians and the geographies of migrant creative labor - De Dios, Anjeline
This thesis provides a labor and cultural geography of creative production at the global periphery. The author characterizes one such peripheral performance sector (live music entertainment in leisure venues such as theme parks, hotels, and cruise ships) as a complex migrant labor economy, wherein the value of creative labor is unevenly segmented by race, gender, and other social categories of embodied difference. In particular, the author argues that the dominance of overseas Filipino musicians (OFMs) in the Asian market for live music entertainment demonstrates the sociospatial processes which configure labor as a flexible resource optimized for the precarious post-Fordist conditions of transnational service and creative work.